2022
DOI: 10.1111/jocd.15546
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Jessener solution versus intralesional steroid in treatment of alopecia areata

Abstract: Background Alopecia areata is an autoimmune condition that causes non‐scarring hair loss. To date, there is no single cure and treatment remains challenging. Objectives To evaluate the efficacy of Jessener solution versus intralesional steroid in treatment of Alopecia Areata. Methods This study included 40 patients who presented with multifocal patchy alopecia areata (AA). For each patient, three patches were randomly selected to be treated one with intralesional steroid, another with topical Jessner solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Alopecia areata (AA), characterized by patchy hair loss from the scalp, is an autoimmune condition precipitated by loss of immune privilege in the hair bulge leading to concentrates of natural killer (NK) cells within hair follicles [ 11 , 12 ]. In the present study, new onset AA and recurrent AA were among the reported hair loss features among participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alopecia areata (AA), characterized by patchy hair loss from the scalp, is an autoimmune condition precipitated by loss of immune privilege in the hair bulge leading to concentrates of natural killer (NK) cells within hair follicles [ 11 , 12 ]. In the present study, new onset AA and recurrent AA were among the reported hair loss features among participants.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover; this exaggerated production of IFNs can contribute to suppressing immunity and further promoting the development of AA. These findings suggest a potential role of vaccines to trigger autoimmunity, as observed in patients vaccinated for hepatitis B and hepatitis A that showed a significantly higher prevalence of alopecia areata [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A follow‐up visit was performed 1 month after treatment, and hair growth on the left and right sides of the scalp was obtained for each patient using a trichoscope (Beining, Nanjing) 23 according to the literature. The number of new hair growths and malnourished hairs was recorded under the trichoscope by two dermatologists who did not participate in the CGF preparation and administration.…”
Section: Methodsmentioning
confidence: 99%